Penentuan Kadar Logam Berat Merkuri (Hg) Dan Cadmium (Cd) Dalam Kosmetik Dengan Atomic Absorption Spectroscopy (AAS): Determination of Heavy Metals Mercury (Hg) And Cadmium (Cd) In Cosmetics With Atomic Absorption Spectroscopy (AAS) - Wulandari, Deyana Dyah; Andini, Ary; Puspitasari, Adela (Universitas Muhammadiyah Sidoarjo, 2018)
Cosmetics are materials intended for use on the outside of the human body or teeth and mucous membranes of the mouth especially to cleanse, scent, change the appearance and / or improve body odor or protect or nourish the body in good condition. In cosmetics can contain harmful active ingredients, one of them is heavy metal. In this study we tested the heavy metals content of mercury and cadmium on cosmetic samples sold in the online market using Atomic Absorption Spectroscopy (AAS) with wavelengths of 253,7 nm for mercury and 228,8 nm for cadmium. Result showed that from 10 cosmetic samples, there were no cosmetic products containing heavy metals mercury and cadmium above the predetermined maximum limit.